Three Unrelated Patients of Roma Ethnicity from a Single Center Carrying the Same Deletion in MYD88 Gene: A Founder Effect? - Roberta Romano; Francesca Cillo; Laura Grilli; Alessio Ciaccio; Lorenzo Bufalo; Elisabetta Toriello; Antonio De Rosa; Carmen Rosano; Emilia Cirillo; Giancarlo Blasio; Marika Comegna; Carmela Di Domenico; et al. (Life)
MyD88 deficiency is a rare inborn error of immunity (IEI) characterized by susceptibility to pyogenic infections without overt signs of inflammation. Half of the reported patients belong to Roma descent, an itinerant ethnic group living mostly in Europe, with an increased risk of childhood mortality due to limited access to healthcare services. We describe three unrelated patients from the Campania region in Italy with MyD88 deficiency, all belonging to Roma descent and displaying severe or recurrent infections in early infancy. They underwent a comprehensive immunological work-up including targeted next-generation sequencing for IEIs that identified a homozygous pathogenic in-frame deletion c.157_159del p.(Glu53del) in MYD88 gene, already described in this ethnic group, suggesting a founder effect. A high level of alert should be kept in patients of Roma ethnicity with early onset severe infections. Moreover, being associated with increased Immunoglobulin E (IgE) levels, this condition should be included in the differential diagnosis of Hyper-IgE syndromes.